2023
DOI: 10.3390/biomedicines11061729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Regenerative Capacity in Rabbit Femoral Defect Using Thermally Disinfected Bone Human Femoral Head Combined with Platelet-Rich Plasma, Recombinant Human Bone Morphogenetic Protein 2, and Zoledronic Acid

Abstract: This research aimed to assess the effect of bone allograft combined with platelet-rich plasma (PRP), recombinant human bone morphogenetic protein-2 (rhBMP-2), and zoledronic acid (Zol) on bone formation. A total of 96 rabbits were used, and femoral bone defects (5 mm) were created. The rabbits were divided into four groups: (1) bone allograft with PRP (AG + PRP), (2) bone allograft with rhBMP-2 5 μg (AG + BMP-2), (3) bone allograft with Zol 5 μg (AG + Zol), and (4) bone allograft (AG). A histopathological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Wang's study [41] found in a New Zealand rabbit model that injection of PRP after core decompression promotes the recovery of endosteal trabecular structures in the femoral head. As well, Saginova's study showed that PRP in combination with bone allografts significantly promoted the early stages of bone defect healing [42].…”
Section: Discussionmentioning
confidence: 90%
“…Wang's study [41] found in a New Zealand rabbit model that injection of PRP after core decompression promotes the recovery of endosteal trabecular structures in the femoral head. As well, Saginova's study showed that PRP in combination with bone allografts significantly promoted the early stages of bone defect healing [42].…”
Section: Discussionmentioning
confidence: 90%
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%